SOCIAL AND HUMANITARIAN EXPERTISE TECHNOLOGY FOR EVALUATING EDUCATIONAL ENGINEERING DESIGN ACTIVITIES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In the article, modern problems of pedagogical engineering design and ways of its improvement are considered in the context of innovative technology of the organization of socio-humanitarian expertise and pedagogical engineering design, as well as the formation of creative project activity of a modern engineer-teacher.